2003
DOI: 10.17705/1cais.01111
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Information Technology Infrastructure Flexibility on Strategic Alignment and Application Implementations

Abstract: IT infrastructure flexibility is now being viewed as an organizational core competency that is necessary for organizations to survive and prosper in rapidly-changing, competitive, business environments. Using data from 200 U.S. and Canadian companies, this study examines the impact of the four components of IT infrastructure flexibility (compatibility, connectivity, modularity, and IT personnel) on strategic IT-business alignment and the extent to which various applications are implemented within an organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 26 publications
4
85
0
4
Order By: Relevance
“…However, it is likely that IR drives governance choice, which in turn drives technological capabilities, or IR interacts with governance choice to drive technology choices in the relationship. 11 The choice of technological capabilities is not the focus of the current study, but future research could examine these selection models in greater detail.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is likely that IR drives governance choice, which in turn drives technological capabilities, or IR interacts with governance choice to drive technology choices in the relationship. 11 The choice of technological capabilities is not the focus of the current study, but future research could examine these selection models in greater detail.…”
Section: Resultsmentioning
confidence: 99%
“…Task modularity [7,11,19] Extent to which the task (a) is shared among business units/functions, (b) maintains interfaces with other organizational processes, and (c) can be executed and managed independently of other organizational processes Technological capabilities [4,76] 1. Percentage of transactions with the service provider that are electronically transmitted (scale: 1 = <5%, 7 = >80%) 2.…”
Section: Relational Uncertaintymentioning
confidence: 99%
“…This mechanism has been the subject of several studies and has been shown to support mutual understanding and relational linkage by ensuring that business and IT discuss and define key goals together (e.g., Reich and Benbasat, 1996;Chung et al, 2003). Such goals are better understood and accepted by both sides.…”
Section: Informal Integration Mechanismsmentioning
confidence: 99%
“…3.70 0.981 −0.865 0.778 (Broadbent and Weill, 1993;Chung et al, 2003) Business understanding of IT personnel component of social business-IT alignment ITBU1 IT employees are able to interpret business related problems and develop solutions.…”
Section: Appendixmentioning
confidence: 99%
“…There exists a reasonably extensive body of literature considering what is required in different circumstances (see for example Chung et al 2003;Brancheau et al 1996;Henderson and Venkatraman 1994). Interestingly though, according to Ciborra (2000), limited effort has been directed to identifying what actually characterises an infrastructure.…”
Section: The Defining Characteristics Of Infrastructurementioning
confidence: 99%